ANALYSIS OF QUALITY OF SERVICE (QoS) ON THE INTERNET NETWORK (Universitas Nahdlatul Ulama Lampung, 2018)
The goal was knew the problems which was quite risky as in terms of accessing the Internet. Therefore to know the quality of the Internet network Wireless LAN to do analysis of network performance that emphasizes how monitoring and assesing Wireless LAN network performance by measuring parameters of bandwidth, delay, and packet loss. In this study, the researcher used action research or action research as research method to describe, interpret and explain a situation or circumstance in the Wireless LAN network in STAIN Metro and analyzing the results of the calculation of the Wireless LAN network downtime to change or intervention with the aim to determine factor- factors that affect Reliability, Maintainability and Availability in the Wireless LAN network so it can provide a better network service. Packet loss network ranged between 32% - 34% occurs caused of a collision / impact packet data or each data on the network. It caused of the traffic network that increase at 10:13 until 11:15 by the number of students who access the Internet network. Beside the ingkcreasing of users, other factor was accessing content on the Internet network can be the affect bandwidth needs. Kinds of content are accessible users that may be the affect the amount of bandwidth. To reduce the packet loss resulting from the collision of the data packets, it is necessary to increase the amount of bandwidth for improving QoS on the network. It needs to setup a web proxy to the site - a site that popular networking sites such as Media Social or video streaming by using a particular port. This is very helpful for data traffic to the WAN or to a LAN